Small pelagic fish responses to fine-scale oceanographic conditions: implications for the endangered African penguin - (:unkn) unknown (My University, 2017)
Small pelagic fish play a significant role in regulating the foraging activities and population trends of marine top predators in upwelling ecosystems, yet there is little information on oceanographic drivers of fish assemblages at temporal and spatial scales relevant to their predators. The survival of the Endangered African penguin Spheniscus demersus is closely linked to the availability of pelagic fish prey. This study assesses the influence of oceanographic variables on the spatio-temporal dynamics of pelagic fish in Algoa Bay, South Africa, where half of the world population of African penguins breed on 2 islands, St Croix and Bird. Using small-scale acoustic surveys and an array of underwater oceanographic data recorders spread across the bay during 3 yr, we reveal the complex and variable nature of this system, with fish responding differently to physical processes around each island. Chlorophyll a concentrations were good predictors of relative fish abundance around Bird Island but had little influence around St Croix Island, possibly due to the masking effect of purse-seine fishing around this site. The horizontal distribution of fish schools around Bird Island was more aggregated under upwelling conditions (cooler sea surface temperatures) and the vertical distribution of fish around both islands was strongly influenced by stratification and mean temperatures. Mechanistic drivers of upwelling included northeasterly winds and offshore Natal pulses, both of which are predicted to have an increasingly more significant effect on the suitability of habitat for pelagic fish and associated predators under the influences of climate change and industrial fishing.
Keywords: African Research